Substernal goiter and laryngopharyngeal reflux - Rodrigues,Mariana Gonçalves (2017)
ABSTRACT Objective This study aims to compare the prevalence of laryngopharyngeal reflux signs between two groups of patients undergoing thyroidectomy for voluminous goiter: substernal goiters and voluminous cervical goiter without thoracic extension. Subjects and methods A retrospective case-control study was performed with data retrieved of the charts of the patients submitted to thyroidectomies occurred at a tertiary care center (Head and Neck Surgery Department, University of São Paulo Medical School) between 2010 and 2014. The selected thyroidectomies were allocated in two groups for study: patients with substernal goiters and patients with voluminous cervical goiter without thoracic extension. Cervical goiters were selected by ultrasonography mensuration. Clinical criterion was used to define substernal goiter. Results The average thyroid volume in patients with substernal goiter was significantly greater than the average volume in patients with only cervical goiter (p < 0.001). The prevalence of signs of reflux laryngitis at laryngoscopy was significantly greater in substernal goiter patients (p = 0.036). Moreover, substernal goiter was considered as the unique independent variable for high reflux laryngitis signs at laryngoscopy (OR = 2.75; CI95%: 1.05-7.20; p = 0.039) when compared to only cervical goiter patients. Conclusion This study shows a significant association between substernal goiters and signs of laryngopharyngeal reflux at preoperative laryngoscopy. Therefore, when compared with voluminous cervical goiters, the substernal goiters increase the chance of reflux laryngitis signs in patients.